Research on characteristics of industrial IoT wireless channel - Yiqian LI; Liu LIU; Huiting LI; Kun ZHANG; Ze YUAN (物联网学报, 2019)
Nowadays,the industrial IoT has become the key competitiveness of the country,and the intelligent manufacturing industry is accelerating.As the information transmission channel in the industrial IoT system,wireless technology plays a strong supporting role in the industrial field.Firstly,the wireless channel characteristics of industrial scene were introduced.Then the propagation characteristics in different frequency bands were analyzed and the main adjustment frequency bands for the initial deployment of industrial private networks were suggested.The causes,influencing factors and value ranges of the large-scale fading and small-scale fading were summarized,and corresponding parameters of the wireless channel characteristics of industrial IoT were summarized.